Caffeinated chewing gum increases repeated sprint performance and augments increases in testosterone in competitive cyclists - Paton, C. D.; Lowe, T.; Irvine, A. (European Journal of Applied Physiology, 2010)
This investigation reports the effects of caffeinated chewing gum on fatigue and hormone response during repeated sprint performance with competitive cyclists. Nine male cyclists (mean ± SD, age 24 ± 7 years, VO2max 62.5 ± 5.4 mL kg-1 min-1) completed four high-intensity experimental sessions, consisting of four sets of 30 s sprints (5 sprints each set). Caffeine (240 mg) or placebo was administered via chewing gum following the second set of each experimental session. Testosterone and cortisol concentrations were assayed in saliva samples collected at rest and after each set of sprints. Mean power output in the first 10 sprints relative to the last 10 sprints declined by 5.8 ± 4.0% in the placebo and 0.4 ± 7.7% in the caffeine trials, respectively. The reduced fatigue in the caffeine trials equated to a 5.4% (90% confidence limit ±3.6%, effect size 0.25; ±0.16) performance enhancement in favour of caffeine. Salivary testosterone increased rapidly from rest (~53%) and prior to treatments in all trials. Following caffeine treatment, testosterone increased by a further 12 ± 14% (ES 0.50; ± 0.56) relative to the placebo condition. In contrast, cortisol concentrations were not elevated until after the third exercise set; following the caffeine treatment cortisol was reduced by 21 ± 31% (ES -0.30; ± 0.34) relative to placebo. The acute ingestion of caffeine via chewing gum attenuated fatigue during repeated, high-intensity sprint exercise in competitive cyclists. Furthermore, the delayed fatigue was associated with substantially elevated testosterone concentrations and decreased cortisol in the caffeine trials.